Implementation of Students Character Education Through Citizency Education Learning in Primary Schools - Suryani Sukamto, Mey; Karolina, Sintia (International Journal of Students Education, 2023)
This study aims to further study and analyze the relationship between the application of character education in Civics learning in elementary schools. In addition, this research analyzes all the efforts that have been made by teachers and basic education institutions in Indonesia to implement character education, especially in Civics learning in elementary schools. This research was conducted using descriptive qualitative methods. The theory or core of this discussion comes from literature or literature studies from various relevant sources, such as books, journals and articles. Studies show that planning and implementing learning determines the application of character education in citizenship education. The character values in the RPP are applied by the teacher in the planning process. The inhibiting factors for teachers in implementing character education are students' lack of self-awareness in obeying regulations, students' motivation to learn is lacking and awareness of those responsible for carrying out assignments is still lacking. Efforts that teachers must make in implementing character education are obeying the rules given and paying attention to students and giving warnings to students who violate school rules.